CLINICAL AND LABORATORY CHARACTERISTICS OF INFECTIOUS MONONUCLEOSIS IN PATIENTS IN THE SAMARKAND REGION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Infectious mononucleosis is a widespread disease most often caused by the herpes virus Epstein-Barr (EBV), affecting 80-90% of the population. With timely and accurate diagnosis of infectious mononucleosis, the effectiveness of treatment of infected patients is manifested by a decrease in the duration of fever, the severity of proliferative syndrome in the lymph nodes, and a more rapid cessation of the cytolysis process.